2025 Korean Thyroid Association Management Guidelines for Radioactive Iodine Therapy in Patients with Hyperthyroidism - Kyeong Jin Kim; Eyun Song; Mijin Kim; Hyemi Kwon; Eu Jeong Ku; Hyun Woo Kwon; Jee Hee Yoon; Eun Kyung Lee; Won Woo Lee; Young Joo Park; Dong-Jun Lim; Sun Wook Kim; et al. (Endocrinology and Metabolism, 2025)
Hyperthyroidism is a condition marked by excessive thyroid hormone production, most commonly due to Graves’ disease. Treatment options include antithyroid drugs (ATD), radioactive iodine (RAI) therapy, and thyroidectomy. To develop standardized clinical recommendations for RAI therapy with a focus on safety, efficacy, and monitoring, the Korean Thyroid Association formed a task force to create evidence-based guidelines. Six key clinical questions were identified through expert consensus, and a systematic literature review from 2013 to 2022 was conducted. Clinical indications for RAI therapy were categorized into three groups: strongly recommended, may be considered, and not recommended. A fixed dose of 10 to 15 mCi is recommended. Although a strict low-iodine diet is unnecessary, iodine-rich foods should be avoided for at least 1 week before treatment. ATD should be stopped 3 to 7 days before RAI and may be resumed in select cases. Prophylactic glucocorticoids are recommended for patients with mildly active thyroid eye disease and may be considered for others at risk. Thyroid function should be monitored at 4–6 weeks post-treatment, every 2–3 months until stabilized, and then every 6–12 months. These guidelines highlight recent advances and underscore the importance of individualized treatment based on clinical features, comorbidities, and patient preferences in Korea.